The Influence Of Environment On Personality Development In Easy A (2010) Movie Directed By Will Gluck: A Behaviorist Perspective - Trisnawati, Dyah (2012)
In this study, the researcher attempts to explore the influences of the environment on the major character Olive Penderghast in the Easy A movie. The objective of the study is to analyze Olive Penderghast in Easy A movie based on the structural element and to analyze the major character behavior based on the psychological approach, especially behaviorist perspective. In analyzing Olive Penderghast the writer uses behaviorist approach and qualitative method. The object of the research is the behavior of the major character derived from Easy A movie published in 2010, directed by Will Gluck and was shot at Screen Gems studios. The data are literary data that consist of primary and secondary data. Easy A movie itself, meanwhile the secondary one includes references and materials related to the study picking up from the books or internet. The methods used for collecting data are library research and documentation. The technique of data analysis is descriptive analysis. The result of the study reveals the life of Olive Penderghast who gets some influences from her new environment after she lied about losing her virginity to her friends. Easy A represents Will Gluck's response to the role of environment in influencing and shaping someone's behavior.